2020
DOI: 10.48550/arxiv.2011.08948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational Constraints on Black Hole Spin

Christopher S. Reynolds

Abstract: The spin of a black hole is an important quantity to study, providing a window into the processes by which a black hole was born and grew. Further, spin can be a potent energy source for powering relativistic jets and energetic particle acceleration. In this review, I describe the techniques currently used to detect and measure the spins of black holes. It is shown that:• Two well understood techniques, X-ray reflection spectroscopy and thermal continuum fitting, can be used to measure the spins of black holes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 129 publications
(168 reference statements)
2
23
1
Order By: Relevance
“…The recently updated measurements (Miller-Jones et al 2021) of the BH mass, as well as its spin a * and companion mass, are marked in blue (at 68% credibility). The currently reported BH spin is very extreme, i.e., a * > 0.983, and it is still consistent with previous measurements (Cantiello et al 2014;Orosz et al 2011;Reynolds 2021). Our finding shows that such high BH spin can be explained by the hypercritical accretion investigated here.…”
Section: Application Of the Hypercritical Accretion Tosupporting
confidence: 92%
See 2 more Smart Citations
“…The recently updated measurements (Miller-Jones et al 2021) of the BH mass, as well as its spin a * and companion mass, are marked in blue (at 68% credibility). The currently reported BH spin is very extreme, i.e., a * > 0.983, and it is still consistent with previous measurements (Cantiello et al 2014;Orosz et al 2011;Reynolds 2021). Our finding shows that such high BH spin can be explained by the hypercritical accretion investigated here.…”
Section: Application Of the Hypercritical Accretion Tosupporting
confidence: 92%
“…To date the BH mass of Cygnus X-1 has exceeded the previously highest measured one in the X-ray binary for the extragalactic system M33 X-7. We note that the BH dimensionless spin recently reported is extremely high, a * > 0.9985 (Miller-Jones et al 2021), which is consistent with the previous measurement, namely a * > 0.983 (Reynolds 2021;Gou et al 2014;Cantiello et al 2014;Orosz et al 2011;Zhao et al 2021). In addition, it has been found that the surface helium-to-hydrogen ratio is about more than a factor of two relative to the solar composition (Shimanskii et al 2012).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Far from the horizon, a • is a higher order correction to the gravitational potential, challenging to observe even for resolved S-star orbits in the Milky Way (Merritt et al 2010), and impossible for unresolved stellar orbits around extragalactic SMBHs. Iron K-α spectroscopy allows spin measurements in bright AGN (Reynolds 2020), which, however, may not be representative of the SMBH population (Berti & Volonteri 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the spin in a black hole (BH) is one of the ★ E-mail: yash@iucaa.in important challenges in X-ray astronomy. Estimates of the spin can be made using spectroscopic methods in which either the relativistic broadening of the Fe K𝛼 line is measured or the continuum X-ray emission is modelled with thermal components (Miller et al 2009;Reynolds 2020). In both cases the innermost radius of the disk is measured and is assumed identical to the innermost stable circular orbit (ISCO).…”
Section: Introductionmentioning
confidence: 99%